Pristine dwarf galaxy survey – I. A detailed photometric and spectroscopic study of the very metal-poor Draco II satellite. Issue 2 (27th July 2018) - Longeard, Nicolas; Martin, Nicolas; Starkenburg, Else; Ibata, Rodrigo A; Collins, Michelle L M; Geha, Marla; Laevens, Benjamin P M; Rich, R Michael; Aguado, David S; Arentsen, Anke; Carlberg, Raymond G; Côté, Patrick; et al.
ABSTRACT: We present a detailed study of the faint Milky Way satellite Draco II (Dra II) from deep CFHT/MegaCam broad-band g and i photometry and narrow-band metallicity-sensitive CaHK observations, along with follow-up Keck II/DEIMOS multi-object spectroscopy. Forward modelling of the deep photometry allows us to refine the structural and photometric properties of Dra II: the distribution of stars in colour–magnitude space implies Dra II is old (13.5 ± 0.5 Gyr), very metal-poor, very faint (L_V = 180 ^+124_-72 L_ ), and at a distance d = 21.5 ± 0.4 kpc . The narrow-band, metallicity-sensitive CaHK Pristine photometry confirms this very low metallicity ([Fe/H] = −2.7 ± 0.1 dex). Even though our study benefits from a doubling of the spectroscopic sample size compared to previous investigations, the velocity dispersion of the system is still only marginally resolved (σ _vr5.9 km s^-1 at the 95 per cent confidence level) and confirms that Dra II is a dynamically cold stellar system with a large recessional velocity (v_r= -342.5^+1.1_-1.2 km s^-1 ). We further show that the spectroscopically confirmed members of Dra II have a mean proper motion of (μ _α ^*, μ _δ)=(1.26 ± 0.27, 0.94 ± 0.28) mas/yr in the Gaia DR2 data, which translates to an orbit with a pericentre and an apocentre of 21.3 ^+0.7_-1.0 and 153.8 ^+56.7_-34.7 kpc, respectively. Taken altogether, these properties favour the scenario of Dra II being a potentially disrupting dwarf galaxy. The low-significance extra-tidal features we map around the satellite tentatively support this scenario.